Constitutional Protection of Cultural Heritage in Indonesia: The Role of Museums in Preserving National Identity and Public Welfare - Ristawati, Rosa; Salman, Radian; Fitriany, Shafyra Amalia; Taskesen, Suat (Sriwijaya Law Review, 2025)
Cultural heritage is a fundamental asset in promoting cultural diversity and facilitating access to education, social values, science, technology, and tourism. Museums play a pivotal role in preserving cultural heritage and fulfilling constitutional obligations, as enshrined in the Indonesian Constitution. Protecting cultural heritage is essential for maintaining national identity and upholding citizens' constitutional rights, particularly in education and cultural participation. This study analyses the constitutional framework and government policies related to cultural heritage protection, with a specific focus on museums in Indonesia. Employing a statute-based and comparative approach, the research examines constitutional provisions such as Article 18B(1) of the Indonesian Constitution, which mandates the state’s responsibility to preserve cultural heritage and safeguard indigenous communities' rights. Despite this constitutional obligation, challenges such as limited financial resources, inadequate maintenance, and institutional constraints hinder the effective operation of museums. The findings emphasize that strengthening museums is not only necessary for heritage conservation but also for fostering national and local values that define Indonesia’s constitutional identity. The study argues that the government must implement more comprehensive policies and allocate sufficient resources to enhance museums’ role in cultural preservation, ensuring their sustained contribution to public welfare and national development.